ANALISIS PELAKSANAAN PROGRAM KELUARGA HARAPAN DI KABUPATEN BREBES TAHUN 2014 - Ghina Febrina; Budi Setiyono; Ahmad Taufiq (Journal of Politic and Government Studies, 2016)
Family Hope Program is a conditional cash transfer program which has theprimary objective is to break the chains of poverty on very poor family (KSM) bychanging the way of life very poor family (KSM) to be more concerned withhealth and education where education and health are the two aspects that canimprove the quality of Human Resources. The purpose of this study was todetermine the results of the implementation of the Family Hope Program inBrebes, whether the program is in accordance with the theory of policyimplementation by George C. Edward III as well find out if PKH able to reducepoverty in Brebes and see what are the factors that influence in theimplementation of PKH in Brebes.The method used in this research is descriptive qualitative. The study wasconducted in Dinsosnakertrans Kab. Brebes, UPPKH Kab. Brebes, Kec.Bulakamba and Kec. Kersana with sources as many as 13 people coveringDinsosnakertrans Head of Social Assistance, Operator Coordinator PKH,Coordinator Assistants District, Companion PKH, Waiter Education, Healthwaitress and PKH participants. And to techniques of data collection is done byinterviews, documentation and literature.Based on the research results, the implementation of the PKH in Brebes are inaccordance with the theory of policy implementation by George C. Edward III inwhich almost all the variables of implementation have been met. However PKHhas not been able to reduce poverty in Brebes because it was influenced by thelow quality of very poor family (KSM) and the misuse of the aid committed bysome participants PKH.The results of this study are expected to provide benefits both the community andthe parties involved (UPPKH and Government). Based on these results, theauthors propose recommendations are expected in their sustainability programswith empowerment very poor family (KSM) to create a standalone program;increased participation of all parties involved; fulfillment facilities related toUPPKH UPPKH district and sub-district; the use of basic data in accordance witha program that does not happen misplaced.